Chapter Smarticon: a Digital Eco-System for Cultural Heritage. Iconographic Convergences in Art and in World Religions - Penco, Sara (Proceedings e report, 2018)
The recovery of the history of humanity goes through the comprehension of ancient testimonies handed down to us in artistic representations. The innovative tool par excellence is the technologies. Smarticon is an Italian patent for method in charge of studying historical analysis (originated from the morphology of the concept), of examining the phenomenology analysis (which results in the typology and exceeds it) and to the comparative research (which allows to arrive at the hermeneutics ). The comprehension of the transitory meaning of each event is entrusted to the historian who, by recomposing the phenomena, is also able to codify the comparative meanings.